2014
DOI: 10.1111/pbr.12157
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × year interaction and broad‐sense heritability of architectural characteristics in rose bush

Abstract: The effect of genotype factors, year and their interaction was assessed on six architectural variables of eight cultivars of rose bush. Plants were grown in pots in a greenhouse in the spring of 2011 and 2012, two highly contrasted years in terms of the quantity of cumulative radiation, with a relative deviation (for 2012 compared to 2011) ranging from À24.6% (April) to +13.7% (March). Their architecture was digitized at two observation scales, the plant and the axis. Highly significant genotype (G) and year (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 26 publications
4
25
2
Order By: Relevance
“…This accounted for 60% of total phenotypic variance and was more than twice that of the narrow-sense estimate for this trait (Table 5). Previous studies evaluated the number of long axes (shoots with five or more metamers each which consist of an internode, a node, an axillary bud and a leaf) and the number of determined axes (axes ended in a flower bud or a flower) (Crespel et al, 2013(Crespel et al, , 2014)-which are equivalent to some extent to the number of primary shoots in our study. The broad-sense heritability for the number of long axes and the number of determined axes assessed using eight diploid garden-rose cultivars in the greenhouse by Crespel et al (2014) were 0.70 and 0.64, respectively, and thus were less than the number of primary shoots (H 2 = 0.92) ( Table 5) in our study using segregating populations of diploid garden roses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This accounted for 60% of total phenotypic variance and was more than twice that of the narrow-sense estimate for this trait (Table 5). Previous studies evaluated the number of long axes (shoots with five or more metamers each which consist of an internode, a node, an axillary bud and a leaf) and the number of determined axes (axes ended in a flower bud or a flower) (Crespel et al, 2013(Crespel et al, , 2014)-which are equivalent to some extent to the number of primary shoots in our study. The broad-sense heritability for the number of long axes and the number of determined axes assessed using eight diploid garden-rose cultivars in the greenhouse by Crespel et al (2014) were 0.70 and 0.64, respectively, and thus were less than the number of primary shoots (H 2 = 0.92) ( Table 5) in our study using segregating populations of diploid garden roses.…”
Section: Resultsmentioning
confidence: 99%
“…The broad-sense heritability of rose architectural traits has been estimated using a set of eight diploid rose cultivars grown in pots in a greenhouse (Crespel et al, 2013(Crespel et al, , 2014, a small (98 individuals) F 1 diploid population planted in the field (Kawamura et al, 2011(Kawamura et al, , 2015, and a biparental F 1 tetraploid cut flower population that was planted under greenhouse conditions in the Netherlands and Kenya (Gitonga et al, 2014). In general, researchers found that the architectural traits they measured during the first flush of growth after dormancy (gardenrose situation) or pruning (cut-rose situation) showed a moderate to high broad-sense herita-bility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With further complementary researches, integrated methodological tools to better fulfill consumers' expectations can be sketched for forward thinking growers. The genesis of such tools can stand on the advantages provided by virtual plant modeling devices which integrate genotype and environment interactions' effects on architectural parameters, and their within crop variability (Crespel et al, 2014;Demotes-Mainard et al, 2013). Such devices associated with instrumental 3D characterization related to visual sensory properties could provide interesting support decision tools for guiding cultural practices toward ornamental plants with specified visual characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Impacts of growing practices on some architectural parameters are well-known for numerous plant species. Nonetheless, growers and breeders make use of them more or less empirically, and resulting effects on visual properties from a sensory point of view still poorly studied (Crespel, Le Bras, Relion, & Morel, 2014;Huché-Thélier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%